Interferon-γ release assays for the diagnosis of latent Mycobacterium tuberculosis infection: a systematic review and meta-analysis - Diel, R; Goletti, D; Ferrara, G; Bothamley, G; Cirillo, D; Kampmann, B; Lange, C; Losi, M; Markova, R; Migliori, G B; Nienhaus, A; Ruhwald, M; et al. (The European respiratory journal, 2011)
We conducted a systematic review and meta-analysis to compare the accuracy of the QuantiFERON-TB® Gold In-Tube (QFT-G-IT) and the T-SPOT®.TB assays with the tuberculin skin test (TST) for the diagnosis of latent Mycobacterium tuberculosis infection (LTBI). The Medline, Embase and Cochrane databases were explored for relevant articles in November 2009. Specificities, and negative (NPV) and positive (PPV) predictive values of interferon-γ release assays (IGRAs) and the TST, and the exposure gradient influences on test results among bacille Calmette-Guérin (BCG) vaccinees were evaluated. Specificity of IGRAs varied 98-100%. In immunocompetent adults, NPV for progression to tuberculosis within 2 yrs were 97.8% for T-SPOT®.TB and 99.8% for QFT-G-IT. When test performance of an immunodiagnostic test was not restricted to prior positivity of another test, progression rates to tuberculosis among IGRA-positive individuals followed for 19-24 months varied 8-15%, exceeding those reported for the TST (2-3%). In multivariate analyses, the odd ratios for TST positivity following BCG vaccination varied 3-25, whereas IGRA results remained uninfluenced and IGRA positivity was clearly associated with exposure to contagious tuberculosis cases. IGRAs may have a relative advantage over the TST in detecting LTBI and allow the exclusion of M. tuberculosis infection with higher reliability.